Governança e relações intergovernamentais : a experiência de desenvolvimento e integração regional do estado do Pará (2007 a 2014) - Oliveira, Jorgiene dos Santos (2016)
In the State of Pará, the object of the present research, a significant institutional reform took place in 2007, based on regional decentralization and the search for integrated regional development. Until then, the development and integration models designed for the State were dictated by the federal government, such as the projects executed by the Superintendency for the Development of the Eastern Amazon (SUDAM). In this sense, the main objective of this thesis is to analyze how the governments of the state of Pará from 2007 to 2014 acted to promote regional development. The central question that led to the analysis was: What are the institutional changes of the state governments of Pará in the period from 2007 to 2014 with the objective of integrated regional development? In this study, we assume that the State reform proposed by the government of Pará from 2007 to 2014 was an initiative focused on regional governance, which has an institutional redesign that favors intergovernmental relations both vertically and horizontally Regional development and intraregional integration. Assuming that institutions can contribute to regional development (although limited by institutional constraints), the hypothesis supported by this thesis will be that the State government in Pará, between 2007 and 2014, carried out institutional reforms based on the Strengthening intergovernmental relations for the purpose of regional development. These changes contributed to regional development and were based on regional governance. Thus, it is argued that, because it is an institutional analysis related to regional development and regional integration, the analysis has as its main axis the regional governance paradigm and the theoretical reference of neoinstitutionalism. In this regard, we analyze the institutional, social and environmental dimension of government actions in the period. The methodology used to reach the proposed objective was the qualitative and quantitative analysis of the data on the case of the State of Pará. We started from the analytical model already used in the literature (ABRUCIO, 2010) in relation to the state governments in Brazil. We concluded that the institutional changes proposed by the State governments during the period analyzed sought to favor intergovernmental relations. However, there were factors that limited interlocking and intergovernmental partnerships implemented from initiatives based on regional governance.